The Psychoactive Drugs and Their Use as Doping by High Performance Athletes - L. Santi (Emerging Trends in Drugs, Addictions, and Health)
Introduction: The list of banned substances released and revised by WADA (World Anti-Doping Agency) every year has several classes of drugs, among which many can be considered psychoactive. This study qualitatively analyzes the use of these substances and their effects on the performance enhancement, in multiple ways, of high-performance athletes. Methods: Analysis and review of annual statistical data published by WADA (World Antidoping Agency) and case studies with data provided by cooperating international federations. Results: Many psychoactive drugs have been found in different profiles and sports, used by high performance athletes, associated or not with other classes of drugs for performance enhancement. Conclusions: It was possible to find a correlation between the use of psychoactive drugs and high-performance sports for many reasons, but it is very difficult to trace and limit the profile of the athlete who uses these substances, making prevention and tracking a challenge